Your answer is D
hope this helps
Note: In option A, it should be "+" instead of "(".
Given:
The expression is
![-2x(x+y-3)+3(-x+4y)+y(3x+5y-3)](https://tex.z-dn.net/?f=-2x%28x%2By-3%29%2B3%28-x%2B4y%29%2By%283x%2B5y-3%29)
To find:
The equivalent expression.
Solution:
We have,
![-2x(x+y-3)+3(-x+4y)+y(3x+5y-3)](https://tex.z-dn.net/?f=-2x%28x%2By-3%29%2B3%28-x%2B4y%29%2By%283x%2B5y-3%29)
Using distributive property, we get
![=-2x(x)-2x(y)-2x(-3)+3(-x)+3(4y)+y(3x)+y(5y)+y(-3)](https://tex.z-dn.net/?f=%3D-2x%28x%29-2x%28y%29-2x%28-3%29%2B3%28-x%29%2B3%284y%29%2By%283x%29%2By%285y%29%2By%28-3%29)
![=-2x^2-2xy+6x-3x+12y+3xy+5y^2-3y](https://tex.z-dn.net/?f=%3D-2x%5E2-2xy%2B6x-3x%2B12y%2B3xy%2B5y%5E2-3y)
On combining like terms, we get
![=-2x^2+5y^2+(-2xy+3xy)+(6x-3x)+(12y-3y)](https://tex.z-dn.net/?f=%3D-2x%5E2%2B5y%5E2%2B%28-2xy%2B3xy%29%2B%286x-3x%29%2B%2812y-3y%29)
![=-2x^2+5y^2+xy+3x+9y](https://tex.z-dn.net/?f=%3D-2x%5E2%2B5y%5E2%2Bxy%2B3x%2B9y)
The expression
is equivalent to the given expression.
Therefore, the correct option is A.
(15h^2+10h+25)/(5h)
(15h^2+10h+25)/(5)
(3h^2+2h+5)/(h)
(15h^2+10h+25)/(5h)
(5h)(3h)=15h^2
(10h+25)/(5h)
(5h)(2)=10h
(25)/(5h)=5/h=\=
(15h^2+10h+25)/(5h)= 3h+2, with a remainder of 25
speed is 45 miles per hour. 135/45=3, so the answer is 3hours (A)
2/3 / 1/6
When dividing by a fraction, flip the second fraction over and change divide to multiply:
2/3 x 6/1 = (2 x6) / (3 x 1) = 12/3 = 4
The answer is 4